Multiple sequential light and laser sources to activate aminolevulinic acid for rosacea. (4th July 2016) - Friedmann, Daniel P.; Goldman, Mitchel P.; Fabi, Sabrina G.; Guiha, Isabella
Summary: Background and Aims: The use of multiple, sequential light and laser sources for topical ALA activation in photodynamic therapy (PDT) of rosacea has been largely absent from the literature. The aim of this study was to evaluate ALA‐PDT for rosacea using blue light sequentially with red light, pulsed‐dye laser (PDL), and/or intense pulsed light (IPL). Patients/Methods: Thirty patients (39 treatments) were enrolled in this retrospective, single‐center study. Treatment groups included blue light + PDL, blue light + IPL, blue light + PDL + IPL, or blue light + red light + PDL + IPL. Patient‐reported outcome measures (incidence of adverse events, improvement in rosacea, and improvement in overall skin quality) were obtained via a telephone questionnaire and graded on a 4‐point scale. Results: There was no statistically significant difference in patient‐reported rosacea or overall skin quality improvement. Apart from decreased peeling following blue light + IPL compared to blue light + PDL ( P = 0.041) and blue light + IPL + PDL ( P = 0.005), there were no other statistically significant differences in postprocedure adverse events. Conclusions: The use of multiple, sequential light and laser sources with ALA‐PDT for rosacea, while well tolerated, did not lead to statistically significant improvements in patient‐reported efficacy. Although this retrospective study is limited by a small sample size with disparate patient numbers between groups and no physician‐evaluated outcome criteria, it does demonstrate that multiple light sources with PDT can be safely used in a single session.